Keefektifan Penerapan Modul Ajar Pembelajaran Projek Penguatan Profil Pelajar Pancasila (P5) Berbasis Nilai Kearifan Lokal Kelong Makassar di SMP Negeri 7 Makassar - Nasir, Muhammad (Seminar Nasional LP2M UNM, 2023)
Abstract. The Makassar Kelong local wisdom value-based project learning teaching module was carried out in the Independent Curriculum co-curricular learning which aims to describe the effectiveness of implementing the Makassar Kelong local wisdom value-based project learning teaching module at SMP Negeri 7 Makassar. The preparation of the teaching module in this research has undergone development stages from example 1 of the P5 learning model. This research is quantitative descriptive research used to research a certain population or sample. The field test was carried out in the control class and experimental class with 30 students each. In the control class, the module used still uses a conventional stage model, while in the experimental class the module used has undergone development of activity stages. The results of the research show differences in the character values of the control class and the experimental class using a co-curricular learning assessment format in accordance with the independent curriculum. The product of this research is a project learning teaching module based on the local wisdom values of the Makassar Kelong which has undergone development that has succeeded in increasing the value of the Pancasila student profile in the dimensions of global diversity, mutual cooperation and independence. Keywords: teaching module, Makassar kelong, co-curricular learning